Development of Brochure-Based Teaching Materials on Persuasive Text in Grade 7th Students of Junior High School Dwi Tunggal Tanjung Morawa - Sri Haryati; Malan Lubis; Khairil Ansari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to find out the developmentof brochure-based teaching materials on persuasive text in grade 7th students.The object of this study is grade 7th students of Dwi Tunggal Tanjung Morawa. The result shows that The process of developing the development of brochure-based teaching materials on persuasive text material was carried out in three stages, namely the preliminary study phase, the initial product development and product testing. At the stage of the preliminary study an analysis of the needs of teachers and students was carried out. The results of the needs analysis obtained data that 100% of teachers and students of Junior High School Dwi Tunggal Tanjung Morawa need teaching materials in the Indonesian language learning companion. In the initial product development stage, product design and product validation were carried out to 2 material experts and 2 media design experts. After the validation process, the product is declared feasible for testing. In the third stage, product testing was carried out in three ways, namely individual trials, small group trials and limited field trials. Individual trials obtained an average percentage of 88.19% with the category "Very good", the small group trial received an average percentage of 89.58% with the category "Very Good". Limited field trials received an average percentage of 91.01% with the category "Very Good". Based on these data, obtained appropriate teaching materials to be used by teachers and students in learning.